Effectiveness of a bedaquiline, linezolid, clofazimine ‘core’ for multidrug-resistant TB - C. Zeng; M.A. Hernán; L. Trevisi; S. Sauer; C.D. Mitnick; C. Hewison; M. Bastard; P. Khan; K.J. Seung; M.L. Rich; S. Law; M. Kikvidze; et al. (IJTLD Open)
INTRODUCTION: Costs for nutritional supplements and food were the main driver of costs incurred by TB-affected households in Lao People’s Democratic Republic. This study assessed the impact of nutritional counselling and support on costs incurred by TB-affected households. METHODS: We conducted longitudinal data collection of costs, income, and coping mechanisms of TB-affected households within an intervention study providing nutritional counselling and support for people diagnosed with TB and having a body mass index (BMI) <18.5 kg/m2. Data collection tools were adapted from the WHO’s generic national TB patient cost survey questionnaire to fit a longitudinal study design. Costs were considered catastrophic when they exceeded 20% of annual household income before TB. RESULTS: A total of 268 people treated for drug-susceptible TB were included in the analysis, and the prevalence of BMI <18.5 kg/m2 was 38%. The intervention group had significantly lower nutritional supplement costs and direct non-medical costs after TB diagnosis than the observation group. The intervention group had less progressive catastrophic costs (+23.3 percentage points) than the observation group (+30.9 percentage points). CONCLUSION: Nutritional counselling and support were significantly associated with a reduction in the proportion of TB-affected households facing catastrophic costs due to TB.